2015
DOI: 10.1002/ar.23189
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence of Serous Gland Polymorphism in the Skin of the Tungara Frog Engystomops pustulosus (Anura Leptodactylidae)

Abstract: Three types of serous products were detected in the syncytial cutaneous glands of the leptodactylid tungara frog, Engystomops pustulosus: type Ia, granules with wide halos and variable density cores; type Ib, high density granules without halos; and type II, vesicles containing a finely dispersed product. Ultrastructural evidence revealed that these products were manufactured by different serous gland types and excluded that they represented different steps in the secretory cycle of a single gland type. Indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In the integument of S. similis, the apocrine granular gland resembles those Ib type glands described for Engystomops pustulosus (Cope, 1864) (Delfino et al 2015). In addition, apocrine glands with heterogeneous content occurred in the integument of all species of Scinaxinae.…”
Section: O Albicanssupporting
confidence: 54%
“…In the integument of S. similis, the apocrine granular gland resembles those Ib type glands described for Engystomops pustulosus (Cope, 1864) (Delfino et al 2015). In addition, apocrine glands with heterogeneous content occurred in the integument of all species of Scinaxinae.…”
Section: O Albicanssupporting
confidence: 54%
“…Rejection of frogs was an unexpected result since anurans are readily consumed by Phoneutria spiders [20,33]. However, it has been reported that the frog E. pustulosus possesses defensive glands, which store noxious substances [34], which may have contributed to their avoidance by the spiders. This is supported by observations as the rejection occurred only after the spider bit the frog.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus and many biologically active substances produced in the dermal glands protect body surfaces against desiccation, abrasion, and invasion caused by microorganisms or other predators. [37,38] In this study, we performed scanning electron microscopy (SEM) to examine the epidermal surfaces of the skins of three common indigenous wetland frog species (i.e., Polypedates braueri, Hylarana latouchii, and Fejervarya limnocharis) and one exotic frog species (i.e., P. megacephalus) observed throughout Taiwan (Figure 1 and Figure S1, Supporting Information). The dorsal skin surface of P. braueri is even and smooth (Figure 1a) and exhibits dispersed dotted chromatophores (i.e., pigment cells) under an optical microscope (Figure 1b).…”
Section: Morphological Characteristics Of Slippery Skins Of Wetland Frogsmentioning
confidence: 99%